2019
DOI: 10.1111/cas.14026
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐204‐5p: A novel candidate urinary biomarker of Xp11.2 translocation renal cell carcinoma

Abstract: Xp11.2 translocation renal cell carcinoma (Xp11 tRCC ) is a rare sporadic pediatric kidney cancer caused by constitutively active TFE 3 fusion proteins. Tumors in patients with Xp11 tRCC tend to recur and undergo frequent metastasis, in part due to lack of methods available to detect early‐stage disease. Here we generated transgenic (Tg) mice overexpressing the human PRCC ‐ TFE 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…To investigate roles of ANGPTL2 in development and progression of tRCC, we generated Chd16-Cre/ Rosa LSL-PRCC-TFE3/+ mice that specifically induce the PRCC-TFE3 fusion gene in renal tubular epithelial cells (Supplemental Fig. S1A; Baba et al 2019;Kurahashi et al 2019). Chd16-Cre/Rosa LSL-PRCC-TFE3/+ mice developed renal cell carcinoma characterized by dilated renal tubules and cyst formation by 40 wk of age, with an incidence of 100%, and their median survival time was 344 d. To evaluate ANGPTL2 function in renal cancer progression, we crossed Chd16-Cre/Rosa LSL-PRCC-TFE3/+ mice with ANGPTL2 mutant mice (either Angptl2 −/− or Angptl2 F/F mice) to achieve ANGPTL2 deficiency in either the whole body or specifically in renal tubular epithelial cells, respectively ( Fig.…”
Section: Angptl2 Expression In Tumor Versus Stromal Cells Has Opposinmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate roles of ANGPTL2 in development and progression of tRCC, we generated Chd16-Cre/ Rosa LSL-PRCC-TFE3/+ mice that specifically induce the PRCC-TFE3 fusion gene in renal tubular epithelial cells (Supplemental Fig. S1A; Baba et al 2019;Kurahashi et al 2019). Chd16-Cre/Rosa LSL-PRCC-TFE3/+ mice developed renal cell carcinoma characterized by dilated renal tubules and cyst formation by 40 wk of age, with an incidence of 100%, and their median survival time was 344 d. To evaluate ANGPTL2 function in renal cancer progression, we crossed Chd16-Cre/Rosa LSL-PRCC-TFE3/+ mice with ANGPTL2 mutant mice (either Angptl2 −/− or Angptl2 F/F mice) to achieve ANGPTL2 deficiency in either the whole body or specifically in renal tubular epithelial cells, respectively ( Fig.…”
Section: Angptl2 Expression In Tumor Versus Stromal Cells Has Opposinmentioning
confidence: 99%
“…Genetically engineered mice used in this study were: Angptl2 -/mice (Tabata et al 2009) on a C57BL/6N background, Pirb −/− mice (Endo et al 2008) (kindly provided by Dr. Takai [Tohoku University]) on a C57BL/6N background, Rosa LSL-PRCC-TFE3/+ mice on a C57BL/6N background (Kurahashi et al 2019), Angptl2 F/F mice (Tian et al 2016) on a C57BL/6J background, and Tg mice overexpressing Cre driven by the murine Cad-herin16 promoter (Cdh16-Cre) (Shao et al 2002) on a C57BL/ 6N background. Male C57BL/6N mice were purchased from CLEA (Japan).…”
Section: Animalsmentioning
confidence: 99%
“…Moreover, urinary exosomal miR-126-3p combined with miR-486-5p could discriminate ccRCC from benign lesions (Butz et al, 2016). Similarly, other more recent studies have reported that urinary exosomal miR-30c-5p and miR-204-5p might serve as the diagnostic markers for early-stage ccRCC (in a human study) and Xp11.2 translocation RCC (in a murine model), respectively (Kurahashi et al, 2019;Song et al, 2019). In addition, two consistent studies in humans have revealed that serum exosomal miR-224 and miR-210 could serve as the prognostic and diagnostic biomarkers for ccRCC (Fujii et al, 2017;Wang X. et al, 2019).…”
Section: Renal Cell Carcinomamentioning
confidence: 63%
“…Additionally, the duo of miR-204-5p/211-5p has recently been reported to be involved in resistance to BRAF inhibition (40). Hence, circRNAs harboring target sites for miR-204-5p/211-5p can have important implications for tumor treatment and progression (41,42).…”
Section: Discussionmentioning
confidence: 99%